A New Characterization on g-Frames in Hilbert C*-Modules (Communications in Mathematical Research, 2019)
In this note, we establish a new characterization on g-frames in Hilbert C*-modules from the operator-theoretic point of view, with which we provide a correction to one result recently obtained by Yao (Yao X Y. Some properties of g-frames in Hilbert C*-modules (in Chinese). Acta Math. Sinica, 2011, 54(1): 1–8.).